2012
DOI: 10.1111/apt.12039
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment with self‐expanding metal stents for Crohn's disease strictures

Abstract: SUMMARY BackgroundBalloon dilation (with or without steroid injection) is the endoscopic treatment of choice for short strictures in Crohn's disease (CD). The placement of a stent has only rarely been reported in this setting, and it may be a good alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 20 publications
0
73
0
1
Order By: Relevance
“…The overgrowth of mucosal hyperplastic reaction in uncovered and partially covered SEMS may facilitate the impaction of the stent with difficulties in retrieving and for this reason this type of stent is less than ideal for the treatment of benign strictures [11]. Owing to their flexibility, FCSEMSs are easier to insert and deploy, and removal is simpler owing to absent or negligible hyperplastic tissue overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The overgrowth of mucosal hyperplastic reaction in uncovered and partially covered SEMS may facilitate the impaction of the stent with difficulties in retrieving and for this reason this type of stent is less than ideal for the treatment of benign strictures [11]. Owing to their flexibility, FCSEMSs are easier to insert and deploy, and removal is simpler owing to absent or negligible hyperplastic tissue overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study demonstrated that the placement of self-expandable metallic stents (SEMSs), often fully or partially covered ones, maintained for a duration of 4 weeks is safe and effective therapeutic option for CD strictures refractory to medical treatment with or without balloon dilation. 44 Although SEMSs are effective in the relief of obstruction, studies have revealed that the use of SEMSs is associated with a high rate of spontaneous migrations. 45 Distal stent migration often suggests successful dilation and is not a sign of failure.…”
Section: Endoscopic Stentingmentioning
confidence: 99%
“…Both noncovered and fully covered metal stent have been used as a 'bridge to surgery' or as definitive treatment to relieve obstructing symptoms in CD patients [47][48][49]: the enthusiasm prompted by initial technical success more than 90% is tempered by the potential complications (shorter patency, mucosal hyperplastic reaction and migration). These complications and cost reflections mandate careful consideration prior to utilizing stents for the treatment of CD complications.…”
Section: Stent Positioningmentioning
confidence: 99%
“…Different approaches have been tried to overcome this issue. Branche et al used fully covered self-expanding metal stent with an antimigratory design comprising two noncovered distal collars at the proximal (ileal) and distal (colonic) ends; stents were removed after 7 days in order to avoid impaction of the noncovered part, and symptoms relief was observed in all patients and no migration reported [48]. Endoscopic suture fixation and clip placement have been shown to significantly reduce fully covered stent migration in esophageal disease [50][51][52] and these methods could potentially be applied in CD strictures [53].…”
Section: Stent Positioningmentioning
confidence: 99%